The theoretical framework of GEMBIRA learning model: An impactful insight for Indonesian numeracy movement - Rachmadi Widdiharto; Rully Charitas Indra Prahmana; Nita Isaeni; Sri Adi Widodo; Sotya Mayangwuri; Puri Pramudiani (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
Numeracy literacy is a foundational competency that plays a critical role in early childhood and primary education, enabling students to make sense of and respond to real-life problems embedded with quantitative elements. Despite numerous initiatives aimed at enhancing numeracy skills at these educational levels, such efforts have often been fragmented and lack a coherent pedagogical framework. In response, the Indonesian Ministry of Primary and Secondary Education launched the National Numeracy Movement as a large-scale initiative to improve numeracy learning outcomes. However, a significant gap remains in the form of a clear instructional framework that can guide early childhood and primary educators in implementing this movement effectively within the classroom context. Addressing this gap, the present study proposes a comprehensive instructional framework termed the GEMBIRA model—an acronym for Gali dan Eksplorasi konteks yang dekat dengan siswa (Explore contexts close to students), Muat konten numerasi hasil eksplorasi (Embed numeracy content from exploration), Buat aktivitas yang bermakna (Design meaningful learning activities), Ikuti alur pikir siswa dalam evaluasi (Follow students’ thinking in evaluation), and Rayakan dan Akhiri pembelajaran dengan menyenangkan (Celebrate and conclude the learning joyfully). The GEMBIRA model is theoretically grounded in Ethno-Realistic Mathematics Education, emphasizing the integration of local cultural contexts and realistic mathematical experiences, particularly in numeracy learning. This study employed an integrative literature review method to construct a robust theoretical framework for the model. The resulting framework offers a practical and contextually relevant pedagogical tool for educators to implement the National Numeracy Movement, particularly at the early childhood and primary school levels. By rooting instruction in culturally familiar and mathematically rich contexts, the GEMBIRA model holds the potential to foster stronger foundational numeracy skills and contribute to students’ long-term academic success.